Analisis Perbandingan Kinerja Keuangan Perbankan Syariah Di Asean Melalui Pendekatan Islamicity Performance Index - Agung Maulana (Universitas Nusa Putra, 2023)
This study aims to analyze and compare the condition of Islamic banking financial performance in the ASEAN region using the method of the Islamicity Performance Index. The analytical method used is the analysis of financial ratios and different test analyses using the non-parametric method Kruskal Wallis where first performed the analysis of normality test using Kolmogorov Smirnov analysis and homogeneity using Levene Statistic test. Based on the calculation of different test statistics, the five countries in the ASEAN region have financial performance through different IPI methods significantly, where the seven ratios of PSR, ZPR, EDRQD, EDRBG, EDRLB, II vs NII, and IInc vs NIInc have Sig 2-tailed <0.05. from the calculation of the ratio, the Philippines and Thailand have the value of the ratio of halal income and investment to the revenue, and the haraam investment is the least meaning that the two countries are still doing business through the forbidden, while the PSR ratio, only Indonesia is focused in conducting business through the principle of risk through musyarakah and mudharabah contracts with PSR value> 30%. On this result, the Sharia councils of each country should be more intensive in controlling the compliance of shari'a from the management of Islamic banking business.